Pengembangan Sejumlah Primer untuk Reverse Transcriptase Polymerase Chain Reaction Guna Melacak Virus Flu Burung di Indonesia (DEVELOPMENt OF PRIMERS FOR REVERSE TRANSCRIPTASE POLYMERASE CHAIN REACTION TO DETECT AVIAN INFLUENZA VIRUS IN INDONESIA) - Dharmayanti, Ni Luh Putu Indi; Hartawan, Risza; Hewajuli, Dyah Ayu (Jurnal Veteriner, 2016)
Until recently, two clades of of avian influenza viruses (AIVs) designated as 2.3.2 and 2.2.3 havebeen circulating in Indonesia. Mutations of AIV genes have cretaed many more variants of the virus. It istherefore important to evaluate the appropriate methods used for the detection and diagnosis of AI virusin the field. Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) have been used as a standardmethod for detection of AIV in many laboratories in Indonesia. The success of RT-PCR for detection ofAIV virus is dependent on the nucleotide sequences of primer that match with the circulating of AIVs. Theaims of this study was to develop RT-PCR by designing primers for H5 subtype specific to the circulatingAIVs in the field. The primers were designed using Primer Design software, and optimization andvalidation of the primer were conducted using AIVs that have been characterized in the previous study.The primers were then used RT-PCR using AIV isolates from field samples and their sensitivity andspecificity were then determined. The results showed that the H5 primers designed in this study, H5-IDand H5-NLP, was able to detect the AIVs in field samples better than the H5-specific primers have beenused previously. In conclusion, H5 primers designed based on recent viruses in the field showed betterresults in the detection of AI virus as compared to the previous primers. As AIV-H5N1 subtype in the fieldwill continue to change and evolve, the use of primers designed in this study is recommended for diagnosisof H5 AIV.
Keywords: Development; primer; avian influenza virus; H5 subtype; RT-PCR